2005
DOI: 10.1002/jobm.200410551
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic bacteria inCoffea arabica L.

Abstract: Eighty-seven culturable endophytic bacterial isolates in 19 genera were obtained from coffee plants collected in Colombia (n = 67), Hawaii (n = 17), and Mexico (n = 3). Both Gram positive and Gram negative bacteria were isolated, with a greater percentage (68%) being Gram negative. Tissues yielding bacterial endophytes included adult plant leaves, various parts of the berry (e.g., crown, pulp, peduncle and seed), and leaves, stems, and roots of seedlings. Some of the bacteria also occurred as epiphytes. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
95
2
15

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(119 citation statements)
references
References 53 publications
(45 reference statements)
5
95
2
15
Order By: Relevance
“…However, the frequency of endophytic bacteria has been shown to be lower than isolation of fungi, which could potentially be explained because the conditions of rainfall and temperature were not favorable to obtain maximal bacterial colonization. Similarly, Vega et al (2005) reported that no difference in bacterial colonization was observed between the different parts of plants, which was confirmed by Arnold and Herre (2003) who discussed that rain, humidity, and temperature can influence the occurrence of endophytes.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…However, the frequency of endophytic bacteria has been shown to be lower than isolation of fungi, which could potentially be explained because the conditions of rainfall and temperature were not favorable to obtain maximal bacterial colonization. Similarly, Vega et al (2005) reported that no difference in bacterial colonization was observed between the different parts of plants, which was confirmed by Arnold and Herre (2003) who discussed that rain, humidity, and temperature can influence the occurrence of endophytes.…”
Section: Discussionmentioning
confidence: 73%
“…Bacillus is a Gram-positive, spore-forming, rod-shaped genus with high tolerance to adverse ecological conditions. Previous studies have shown that endophytic bacteria of the genus Bacillus are present in: Coffea arabica L. (Vega et al, 2005), sunflower (Forchetti et al, 2007), cotton (Misaghi and Donndelinger, 1990), potato (Sessitsch et al, 2004), strawberry (Dias et al, 2008), Panaxnoto ginseng (Ma et al, 2013), and citrus plants (Araujo et al, 2001). Among the bioprospection factors, the endophyte Bacillus stands out for phosphate solubilization and auxin production (Dias et al, 2008) and activity against Fusarium oxysporum, Ralstonia sp, and Meloidogyne hapla (Ma et al, 2013).…”
Section: Molecular Identification Of Isolates Based On Partial 16s Rdmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the potential benefit for C. arabica, the community of its endophytic microorganisms has not received much attention. In fact, the only studies so far have been focusing on endophytic bacteria [41], fungal foliar endosymbionts [8] and the presence of ochratoxin producing Penicillium spp. [42] in C. arabica.…”
Section: Discussionmentioning
confidence: 99%